2009
DOI: 10.1128/jb.01259-08
|View full text |Cite
|
Sign up to set email alerts
|

An Essential DnaB Helicase ofBacillus anthracis: Identification, Characterization, and Mechanism of Action

Abstract: We have described a novel essential replicative DNA helicase from Bacillus anthracis, the identification of its gene, and the elucidation of its enzymatic characteristics. Anthrax DnaB helicase (DnaB BA ) is a 453-aminoacid, 50-kDa polypeptide with ATPase and DNA helicase activities. DnaB BA displayed distinct enzymatic and kinetic properties. DnaB BA has low single-stranded DNA (ssDNA)-dependent ATPase activity but possesses a strong 533 DNA helicase activity. The stimulation of ATPase activity appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, these data suggest that fork DNA unwinding by LT may require more than the simple translocation along ssDNA to display the other strand as described in the "exclusion model" that is currently believed to be the case for T7 gp4 and DnaB. 19,40 DNA-dependent coordination mode change for DNA unwinding As a nanomachine, LT helicase couples the energy from ATP binding/hydrolysis to DNA unwinding. Our mutant doping data using ATPase-defective or helicase-defective mutants reveal that LT unwinds DNA with clearly two distinct subunit coordination mechanisms, depending on whether a fork DNA and a blunt-ended ori-DNA serve as the substrate.…”
Section: Dna-dependent Coordination Mode Change For Atp Hydrolysismentioning
confidence: 91%
“…Therefore, these data suggest that fork DNA unwinding by LT may require more than the simple translocation along ssDNA to display the other strand as described in the "exclusion model" that is currently believed to be the case for T7 gp4 and DnaB. 19,40 DNA-dependent coordination mode change for DNA unwinding As a nanomachine, LT helicase couples the energy from ATP binding/hydrolysis to DNA unwinding. Our mutant doping data using ATPase-defective or helicase-defective mutants reveal that LT unwinds DNA with clearly two distinct subunit coordination mechanisms, depending on whether a fork DNA and a blunt-ended ori-DNA serve as the substrate.…”
Section: Dna-dependent Coordination Mode Change For Atp Hydrolysismentioning
confidence: 91%
“…The active fractions were pooled and concentrated by ultrafiltration using a YM-30 membrane. The purified helicase was greater than 98% pure as analyzed by SDS-PAGE 29, 32. The enzyme was verified to be stable for several hours at room temperature, and for at least 12 weeks at−20°C in 20% glycerol storage buffer.…”
Section: Methodsmentioning
confidence: 97%
“…The cloning and expression of the B. anthracis dnaB gene and subsequent purification of the helicase has been described 29. Briefly, the gene was amplified by PCR with primers HCASE45-5′and HCASE45-3′ (Table 6) and B. anthracis genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown by limited proteolytic digestion that a 33-kDa C-terminal fragment retains the DNA-dependent ATPase stimulation activity suggesting that this region may contain the DNA binding domain [25,26]. The ssDNA binding activity of DnaB helicases has been reported in many known helicases [12,[27][28][29][30][31]. B. stearothermophilus DnaB also binds to dsDNA, albeit with less affinity, suggesting diversity in the DNA binding activities of the DnaB helicases [12].…”
Section: Introductionmentioning
confidence: 99%
“…B. stearothermophilus DnaB also binds to dsDNA, albeit with less affinity, suggesting diversity in the DNA binding activities of the DnaB helicases [12]. Binding of ssDNA stimulates the NTPase activity of all the studied DnaB helicases [4,[27][28][29]32,33]. DnaB hexamer forms a ring-shaped structure and it is suggested that ssDNA threads through the central channel of the ring [4,31,34,35].…”
Section: Introductionmentioning
confidence: 99%